2020
DOI: 10.21776/ub.jitek.2020.015.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Chemical and Microstructure Properties of Composite Edible Film Added with Modified Casein

Abstract: Edible film is potentially applied to replace non-biodegradable packaging for animal products, e.g. meat and meat products. The overall objective of this study was to observe the effect of different addition levels of modified casein hydrolysate (casein-catechin complexes) on mechanical (film thickness, water vapor permeability, tensile strength, elasticity), chemical (moisture content, water activity, and solubility) and microstructure properties of composite edible casein film. The edible films were formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This was attributed to the binding of both polymers, resulting in the limited availability of free water. Ideal packaging should maintain low moisture content ranging from 16 to 24% to allow for protecting the packaged product during its shelf life [ 49 ]. Hence, the CS/NaCas composite film in this study possessed the desired moisture content value that has the least effect on food safety and quality.…”
Section: Resultsmentioning
confidence: 99%
“…This was attributed to the binding of both polymers, resulting in the limited availability of free water. Ideal packaging should maintain low moisture content ranging from 16 to 24% to allow for protecting the packaged product during its shelf life [ 49 ]. Hence, the CS/NaCas composite film in this study possessed the desired moisture content value that has the least effect on food safety and quality.…”
Section: Resultsmentioning
confidence: 99%
“…Caseinbased edible films were dissolved with aquadest and the addition of a plasticizer using glycerol. This is the same as previous study which reported that edible films were made dissolving casein in 1 g/50 ml of distilled water [6]. Edible film bovine milk is made by dissolving bovine milk with aquadest, Na 2 HPO 4 and NaH 2 PO 4 .…”
Section: Introductionmentioning
confidence: 63%
“…The solubility of edible films is determined by the basic components of the edible film. The solubility of edible films in can be used as an indicator to measure the resilience, integrity, and ability of edible films in water [6]. Solubility in water is an indication of the hydrophilicity of edible films [17].…”
Section: Solubility In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, corn starch also contains zein which has the ability to inrm a rigid, shiny, abrasion-resistant and greaseresistant film [17][18][19]. Dissolved solids derived from the basic ingredients for edible films production and the increasing number of molecules in solution caused the highest solubility to indicate that edible films were easily decomposed, applied to instant products, and lower water resistance [19][20][21][22]. Note: The numbers followed with different alphabet showed significantly based on DMRT α = 5 %.…”
Section: Edible Film Solubilitymentioning
confidence: 99%